MEKANISME DAN KEABSAHAN TRANSAKSI JUAL BELI E-COMMERCEMENURUT KITAB UNDANG-UNDANG HUKUM PERDATA - Santonius Tambunan (Program Magister Hukum Universitas Lambung Mangkurat, 2016)
The title ofthis studyis themechanismand thevalidity of thetransactione-commerce in terms ofArticle1320Indonesian Civil Law. The research method usedin this studyis the kind ofnormativeresearchthatexaminesthe norms, principles and legaldoctrinesrelating tothe issues raised. Thetype ofresearchthat researchers usein this studyare the type ofresearch on thelevel ofhorizontalsyncisthe norminterms of theInformation and Electronic Transaction Act withthe provisionsof Article1320Indonesian Civil Law.Offer and acceptance are the stages of pre online buying and selling contracts in e-commerce. In this process the good faith of the parties shall take precedence in the transaction. The momentum of the sales contract e-commerce can not be separated from the pre-contract stage. Although the mechanism is different transactions, but in general the contract e-commerce trading has occurred since the purchaser or consumer to send a message of acceptance of the products on offer to the seller (merchant). This suggests that the momentum of buying and selling contracts e-commerce more closely at the theory of acceptance (ontvangstheorie).Subjective terms in the transaction e-commerce are consent of the individuals who are bound thereby and capacity to conclude an agreement. While the objective terms are a specific subject and an admissible cause. Information and Electronic Transaction Act is a lexspecialis provisions of Article1320Indonesian Civil Law. However, in this Act only regulates consent of the individuals who are bound thereby and a specific subject, while capacity to conclude an agreement and an admissible cause has not been accommodated. Therefore, capacity to conclude an agreement and an admissible cause, can refer to the Civil Code as its lexgeneralis. Keywords: E-commerce, Sale and PurchaseTransaction, Mechanism, Validity